Penyuluhan Tentang Kandungan Abon Jamur Tiram Sebagai Pangan Olahan Kaya Zat Gizi - Nurzihan, Nastitie Cinintya; Setyaningsih, Aryanti; Ardya C.S, Hanugrah (Universitas Gajah Putih, Indonesia, 2023)
Abstract One of the problems that often occurs in the community is the problem that is often experienced in preparing healthy food for children and their families. Various ways can be done by processing existing food ingredients so that the fulfillment of consumption can be fulfilled. Fast food or better known as fast food is food that is served in a short time and can be consumed quickly. Oyster mushrooms have a chewy and soft texture and are rich in fiber, so they have the potential to be a source of dietary fiber and protein as a substitute for meat. Efforts have been made to overcome problems in preparing healthy and fast food as well as being economical, including by innovating food products that are easy to obtain. For this reason, it is necessary to provide an approach with the counseling method by demonstrating the content of shredded oyster mushrooms so that it can add to community education to be applied to their respective families. The processing of mushrooms that do not vary is actually one of the causes that has not been used optimally, for this community service activities This community has the potential to be able to add to the public's insight regarding the content of shredded oyster mushrooms which are rich in nutrients.